ANALISIS YURIDIS TENTANG PENCANTUMAN KLAUSULA PROTEKSI DIRI DALAM AKTA NOTARIS - VELIKA MUSTIKA (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. Rudy Haposan3. Madiasa Ablizar A self-protection clause is a clause stating that if there is a statement that is not in accordance with what is stated in the deed, there is a dispute or there are things/statements which have been proven to be incorrect from the complainants themselves, then that will not involve a Notary. refers to the provisions of article 38 paragraph (3) letter c UUJN, the inclusion of the self-protection clause may be included if it is the wish of the intended parties because the deed made for the parties is the wish of the parties, not the desire of the Notary. The Notary is not a party to the deed so that the Notary may not include any clause. The inclusion of the self-protection clause does not provide the benefit of protection for the Notary who lists it in the deed he made.Keyword: Clause, Self-protection, Notary, Notarial deed